2015
DOI: 10.1111/puar.12356
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison of Public and Private Employees’ Work Motives, Attitudes, and Perceived Rewards

Abstract: This article presents a conceptual perspective on the distinctive characteristics of public organizations and their personnel. This perspective leads to hypotheses that public organizations deliver distinctive goods and services that influence the motives and rewards for their employees. These hypotheses are tested with evidence from the International Social Survey Programme in order to compare public and private employees in 30 nations. Public employees in 28 of the 30 nations expressed higher levels of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
1
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 65 publications
5
152
1
12
Order By: Relevance
“…Further studies have explored the relationship between organizational commitment and employee motivation from an international perspective (Bullock, Stritch, & Rainey, 2015;Gagne et al, 2014;Cerase & Farinella, 2009). In a study of employees across 30 countries, Bullock, Stritch, & Rainey found that organizational commitment varied between public and private employees.…”
Section: Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have explored the relationship between organizational commitment and employee motivation from an international perspective (Bullock, Stritch, & Rainey, 2015;Gagne et al, 2014;Cerase & Farinella, 2009). In a study of employees across 30 countries, Bullock, Stritch, & Rainey found that organizational commitment varied between public and private employees.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Bullock, Stritch, and Rainey (2015) surveyed public and private sector employees across 30 countries to determine employee motivation factors. The results of the study indicated that public employees held more concern for the social impact of their job as a major motivational factor.…”
Section: Employee Motivation In the Public Sector Vs The Private Sectormentioning
confidence: 99%
“…Public institutions tend to have other organisational cultures, and its employees have different work motives and attitudes towards their jobs (Bullock, Stritch, & Rainey, 2015). Employees in public organisations are thought to have a unique set of values, attract a particular type of employees, and are motivated by different condition (Vandenabeele, 2007).…”
Section: Exploratory Findingsmentioning
confidence: 99%
“…Employees in the public sector are more motivated by their contribution to the public service and society (Wright, Donald, & Sanjay, 2012). Moreover, public workers place less emphasis on their income (Crewson, 1997) and show less organisational commitment (Bullock et al, 2015). Specifically, the idea that public workers are less committed to their organisation may contribute to the absence of evidence in this case.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…A serious problem is usually the lack of understanding of organizational culture, or in an amendment notice to change staff behaviour (Thatcher and Bagger, 2011;Bullock et al, 2015).…”
Section: Telework Applicationmentioning
confidence: 99%